Exploring Tablet Interfaces for Product Appearance Authoring in Spatial Augmented Reality. Issue 156 (December 2021) - Morosi, Feederico; Carli, Iacopo; Caruso, Giandomenico; Cascini, Gaetano; Dekoninck, Elies; Boujut, Jean-François
Highlights: Application of Spatial Augmented Reality (SAR) in design is still limited. Different interfaces are benchmarked with respect to design application. UIs performance is assessed through diverse subjective and objective metrics. Touch interfaces demonstrate to perform as good as professional solutions Abstract: Users acceptance of innovative product appearance authoring tools based on Spatial Augmented Reality (SAR) is still limited due to their perception of a high technology complexity and a low performance/functionality of the current interaction systems. The integration of SAR technologies in professional design activities is still marginal, though many studies in this field have already proved their potential as supporting tools. To overcome this barrier, efficient means for interacting with the digital images projected onto the surfaces of real objects are essential. The aim of the current study is to respond to this demand by proposing and validating three UI configurations displayed by an unique and portable device embedded with a touch screen. These interface layouts, designed to cooperate with the output of the SAR system and to not affect the well-known benefits of its augmented environment, provide different types of visual feedback to the user by duplicating, extending or hiding the information already displayed by the projected mock-up. The experimental study reported here, performed with a panel of 41 subjects, revealed that accuracy, efficiency and perceived usability of the proposed solutions are comparable with each other and in comparison to standard desktop setups commonly used for design activities. According to these findings, the research simultaneously demonstrates (i) the high performances achieved by the touch device when coupled with a SAR system during the execution of authoring tasks, (ii) the capability of the projected mock-up to behave as an actual three-dimensional display for the real time rendering of the product appearance and (iii) the possibility to freely select - according to the users preference, the design task or the type of product - one of the three UI configurations without affecting the quality of the result.